The evaluation of the undergraduate studies program of the Department of business administration of the Technological Educational Institute (T.E.I.) of Thessaly-Greece by applying a benchmarking approach - Gkountroumpi, Evangelia; Sdrolias, Labros; Škodová Parmová, Dagmar; Aspridis, Georgios; Kakkos, Nikolaos; Cudlínová, Eva; Belias, Dimitrios; Dvořáková Líšková, Zuzana (My University, 2015)
The remarkable and multilateral developmental impact and perspective of H.E.Is is widely known. Moreover, the spread of competence and technological innovation should not be a privilege for a few people who have the possibility of acquiring knowledge and skills from the International Academic Institutions. Unfortunately, raw reality remains the same and in order to be reduced, the “conventional” Academic Institutions ought to evolve constantly and develop more remarkable international collaborations in order to be able to exist, operate and contribute to the strongly competitive environment. Based on the above references, the undergraduate course of the Department of Business Administration, Faculty of Business and Economics, of the Technological Educational Institution (T.E.I) of Thessaly is being evaluated through the Benchmarking process as it has been defined by the Hellenic Quality Assurance & Accreditation Agency (H.Q.A), as well as with the standards of other internationally recognized and accredited institutions (e.g. European Association for Quality Assurance in Higher Education – E.N.Q.A, Chartered Management Institution – C.M.I etc.) in order to detect any deviations that would need specific suggestions and improvement procedures able to make this Department strongly competitive.
Keywords: H.E.Is; Evaluation of Studies Program; Benchmarking; Quality Assurance & Accreditation Agencies; Suggestions–Improvements; Greece